Quantitative radiographic analysis of foraminal re-stenosis after posterior cervical foraminotomy with laminoplasty. (September 2019) - Mizouchi, Tatsuki; Watanabe, Kei; Izumi, Tomohiro; Katsumi, Keiichi; Shoji, Hirokazu; Ohashi, Masayuki; Tashi, Hideki; Hirano, Toru; Yamazaki, Akiyoshi; Endo, Naoto
Highlights: Foraminal space decreased 2 years after posterior foraminotomy with laminoplasty. Foraminal re-stenosis was caused by bone regrowth of the resected facet joint. Loss of PDH less than 1 mm is a risk factor for foraminal re-stenosis. Abstract: Few studies have performed detailed radiographic evaluation of the cause of recurrent cervical radiculopathy. In this study, we aimed to perform quantitative analyses of foraminal re-stenosis after posterior cervical foraminotomy (PCF) concomitant with laminoplasty. Seventy-eight consecutive patients (50 males and 28 females, mean age of 62 years at surgery) with cervical spondylotic radiculomyelopathy who underwent PCF concomitant with open-door laminoplasty were included. A total of 133 foramina undergoing PCF were radiographically evaluated using the following parameters: disc height, focal range of motion at the corresponding disc level, foraminal diameter (FD) and facet joint width (FJW) in the axial view on computed tomography, and re-stenosis rate (RR) of foramina. RR was calculated as follows: (foraminal regrowth at 2 years after surgery)/(foraminal enlargement immediate postoperatively) × 100% (RR2y). FDs preoperatively, postoperatively, and at 2-year follow-up were 2.2, 6.6, and 4.6 mm, respectively, and FJWs were 14.5, 9.0, and 10.6 mm, respectively. Both parameters significantly increased at the 2-year follow-up (p < 0.001). The mean RR2y was 42% (range, −16 to 108%). On logistic regression analysis of risk factors for higher RR2y (>50%), only preoperative posterior disc height (PDH) (OR = 0.33; 95% CI = 0.193–0.563; p < 0.001) was identified. Receiver operating characteristic curve analysis showed that the cut-off value of RR2y 50% was 1-mm PDH (AUC 0.73, sensitivity 52%, specificity 86%, p value < 0.001). After posterior foraminotomy with laminoplasty, the enlarged foraminal space gradually decreased during the 2-year follow-up. Foraminal re-stenosis was mainly due to bone regrowth of the resected facet joint, which is caused by disc degeneration with loss of PDH.